The role of city parks in creating ‘wellbeing societies’: A case study of Piłsudski Park in Łódź, Poland - Kay Smith, Melanie; Kowalczyk-Anioł, Joanna; Janiszewski, Jakub; Grabarczyk, Karolina (Turyzm/Tourism, 2025)
This article examines the role of urban green spaces (UGSs) and city parks in fostering wellbeing among urban residents. UGSs are increasingly being recognized for their contribution to public health, mental wellbeing and social cohesion, and this research fills a gap in the understanding of these benefits in the context of Central and Eastern European cities. The current study presents research on the motivations, patterns of use, chosen activities and wellbeing benefits of visiting the largest city park in Łódź: Marshal Józef Piłsudski Park. The research utilizes a questionnaire-based survey of 238 park users to explore patterns of park use, motivations for visiting and perceived wellbeing benefits. Findings reveal that physical activities, such as walking, are the primary motivation for park visits, while mental benefits like relaxation and stress reduction are highly valued outcomes. Although social interactions are rated lower overall, they are particularly significant for younger and older users, as well as marginalized groups such as unemployed individuals. The study also highlights the role of proximity and the frequency of visits in amplifying wellbeing benefits. Despite the park’s evolving infrastructure, aligning with modern trends, passive recreational activities dominate usage patterns. The research underscores the potential of urban parks to address health and social challenges, advocating inclusive and participatory urban planning. These findings contribute to the broader discourse on sustainable urban development and the creation of ‘wellbeing societies’ through urban green spaces.